Experimental behaviour of stainless steel bolted T-stub connections under monotonic loading. (January 2019) - Yuan, H.X.; Hu, S.; Du, X.X.; Yang, L.; Cheng, X.Y.; Theofanous, M.
Abstract: A comprehensive experimental study on structural behaviour of stainless steel bolted T-stub connections is presented in this paper. A total of 27 stainless steel bolted T-stubs with various geometric configurations were fabricated from hot-rolled stainless steel plates and assembled with stainless steel bolts. Two stainless steel grades − austenitic EN 1.4301 and duplex EN 1.4462, and two other types of stainless steel bolts − A4-70 and A4-80, were introduced in the experimental programme. Tensile coupon tests were performed to determine the material properties of the stainless steel plates and bolts. The bolted T-stub specimens were tested under monotonic loading, and ultimate resistances, plastic deformation capacities and failure modes were obtained. Based on the experimental results, the existing design methods for predicting tension resistances of the bolted T-stub connections, including design provisions in EN 1993-1-8, the continuous strength method (CSM), AISC manual and JGJ 82 and other design formulae for T-stubs with four bolts per row, were all evaluated. It was indicated that all the existing design methods provided generally conservative predictions for stainless steel bolted T-stub connections. Highlights: Monotonic loading tests on 27 stainless steel bolted T-stub connections. The three typical failure mechanisms are observed for stainless steel T-stubs. Key parameters including bolt preload, material grade, flange thickness and bolt diameter are analysed. Evaluation of current design methods for predicting tension resistances of bolted T-stubs.